Public health emergency: social representations among managers of a university hospital - Dirciara Barañano Souza; Clarice Maria Dall'Agnol (Universidade de São Paulo, 2013)
AIM: to comprehend the social representations of public health emergencies among managers who experienced the Influenza A (H1N1) Pandemic of 2009. METHOD: a qualitative case study, with its theoretical and methodological framework based on the Theory of Social Representations. The data was obtained through the techniques of free association and semi-structured interviews, applied individually to managers who worked in different positions of the hierarchical management structure of the institution during the pandemic emergency, a total of 30 participants. RESULTS: thematic content analysis resulted in the following categories: vulnerability, health protection, neglect - gray areas of the public sphere, and integrality. The social representations of public health emergencies attest to continuities that transit the overvalorization of negative discourses linked to the health/education public space, naturalization of the substantial character of the epidemic, and normative managerial action. However, the defense of ongoing education as a necessity associated with emergency management revealed possibilities for change in the technical-scientific perception of the management. CONCLUSIONS: to understand healthcare/nursing workers as political beings, assuming responsibilities in the areas of the macro and micro policies of the State, the university hospitals and the work teams, is a pathway that is emerging for the management of emergencies.